The Effect of Electronic Word of Mouth (E-WOM) and Price Perception on Purchase Decisions of MIXUE Products in the City of Surabaya - Luthfi Ali Akbar; Ugy Soebiantoro; Egan Evanzha Yudha Amriel (PT Inovasi Pratama Internasional, 2023)
This study aims to determine the effect of E-WOM on Mixue Products in Surabaya and the influence of Price perceptions on Purchase Decisions of Mixue Products in Surabaya. The population in this study are consumers of Mixue products in Surabaya. The sample in this study used the slovin formula and found the results of 100 respondents. The method used in this study uses the GForm form. The analysis technique in this study uses PLS (Partial Least Square). The results of this study indicate that the E-WOM indicator variable that has the highest percentage is I often collect review information from consumers online before I buy Mixue products (X1). From the results of the study, it can be concluded that E-WOM contributes to Mixue Purchase Decisions in the City of Surabaya. The more intensity and reviews that mention Mixue products can encourage purchasing decisions about what Mixue Surabaya has provided.